microRNA-203 inhibits migration and invasion of canine tonsillar squamous cell carcinoma cells by targeting SLUG - Noguchi, Shunsuke; Matsui, Asuka (Frontiers in Veterinary Science, 2023)
Objective Squamous cell carcinoma (SCC) occurring in the tonsils (TSCC) has a poorer prognosis than SCC occurring in other regions of the oral cavity (non-tonsillar SCC [NTSCC]) because it easily metastasizes to distant organs. This study aimed to elucidate the molecular mechanisms underlying the migration and invasion of TSCC cells in vitro. Materials and methods This study focused on differential microRNA (miRNA) expression using microRNA microarrays and quantitative polymerase chain reaction in canine TSCC and NTSCC tissues and cell lines. A target gene of the miRNA involved in cell migration and invasion was validated by wound healing, transwell, and luciferase assays. Results miR-203 expression was lower in TSCC tissues than in the normal oral mucosa and NTSCC tissues. Transfection of the miR-203 mimic resulted in the downregulation of mesenchymal marker protein expression and attenuation of cell migration and invasion in TSCC cells, but not in NTSCC cells. A dual-luciferase assay revealed that miR-203 directly targeted the mesenchymal transcription factor SLUG. SLUG overexpression enhances the migration of TSCC cells. Conclusion Our study indicates that the miR-203/SLUG axis may be involved in the metastatic mechanisms of TSCC.